Innovation in Fiqh Muamalah Learning Through Mini Research Method (Research at MA Al-Muhajirin Purwakarta) - R. Marpu Muhyidin Ilyas; Wildan Baihaqi; Nadia Kurnia Fauzia; Badrudin; Qiqi Yuliati Zaqiah (al-Afkar, Journal For Islamic Studies, 2025)
The development of information and communication technology has brought significant changes in various aspects of life, including economic and business activities. E-commerce as a modern internet-based buying and selling transaction model has become an unavoidable phenomenon. This study is a qualitative study with a literature study method and field study that explores the practice of e-commerce and dropshipping at MA Al-Muhajirin Purwakarta. In this method, students are guided to conduct simple research related to certain fiqh topics, collect data from various sources, and present findings in the form of papers, presentations, or posters. This method develops the skills of researching, processing information, and presenting ideas scientifically. From the perspective of muamalah fiqh, e-commerce transactions are a development of the concept of buying and selling (al-bai') which is prescribed in Islam. Buying and selling is defined as the exchange of property for property on the basis of mutual consent ('antaradhin), or transferring ownership of goods with compensation based on the method permitted by sharia. This study is expected to contribute to the enrichment of the treasury of contemporary muamalah fiqh as well as becoming a model for research-based learning innovation in madrasah aliyah.